Bahasa Dalam Dakwah Kh Anwar Zahid Di Youtube Anza Channel (Kajian Sosiolinguistik) - Zulianingtyas, Elda Firnanda; Surana, Surana (Jurnal Online Baradha, 2023)
Language as a means of expressing the human spirit. There is a wide variety of languages used in society. The diversity of language can be found in KH Anwar Zahid's da'wah which is the object of study in this study. This study aims to (1) Know the form of base variety in KH Anwar Zahid's preaching on Youtube Anza Channel, (2) Know the form of code switching in KH Anwar Zahid's preaching on Youtube Anza Channel, and (3) Know the form of code mix in KH Anwar Zahid's preaching on Youtube Anza Channel. This study uses descriptive qualitative research methods and data collection techniques using observation, listening and recording techniques. This research data analysis technique is by observing the object of research longer and using literature study. The data source of this research comes from KH Anwar Zahid's da'wah video on Youtube Anza Channel and research data in the form of words used by KH Anwar Zahid in the video. The results of this study show the form of language variety, including Javanese language variety, Indonesian language variety, and Arabic language variety, the form of code switching including internal code switching of Indonesian-Javanese language, external code switching of Indonesian-Arabic language and external code switching of Javanese-Arabic language and the form of code mix including Javanese-Indonesian-Arabic code mix, Javanese-Indonesian-English code mix and Javanese-Indonesian-Arabic-English code mix. Keywords: Language variety, code switching, code mixing Bahasa sebagai sarana dalam mengepresikan jiwa manusia. Ada beraneka ragam bahasa yang digunakan dalam masyarakat. Keanekaragaman bahasa tersebut bisa ditemukan dalam dakwah KH Anwar Zahid yang menjadi objek kajian dalam penelitian ini. Penelitian ini bertujuan (1) Mengetahui wujud ragam basa dalam dakwah KH Anwar Zahid di Youtube Anza Channel, (2) Mengetahui wujud alih kode dalam dakwah KH Anwar Zahid di Youtube Anza Channel, dan (3) Mengetahui wujud campur kode dalam dakwah KH Anwar Zahid di Youtube Anza Channel. Penelitian ini menggunakan metode penelitian deksriptif kualititaf dan teknik pengumpulan data menggunakan teknik observasi, simak dan catat. Teknik analisis data penelitian ini yaitu dengan mengamati lebih lama objek penelitian dan menggunakan studi pustaka. Sumber data penelitian ini berasal dari video dakwah KH Anwar Zahid yang ada di Youtube Anza Channel dan data penelitian berupa kata-kata yang digunakan oleh KH Anwar Zahid dalam video tersebut. Hasil penelitian ini menunjukkan wujud ragam bahasa, diantaranya ada ragam bahasa Jawa, ragam bahasa Indonesia, dan ragam bahasa Arab, wujud alih kode diantaranya alih kode intern basa Indonesia-Jawa, alih kode ekstern basa Indonesia-Arab dan alih kode ekstern basa Jawa-Arab dan wujud campur kode diantaranya campur kode Jawa-Indonesia-Arab, campur kode Jawa-Indonesia-Inggris dan campur kode Jawa-Indonesia-Arab-Inggris. Kata Kunci: Ragam bahasa, alih kode, campur kode